Effects of Cry1Fa Bt resistance on the reproductive output of Spodoptera frugiperda - Ribas, Natália de Souza (2018)
The transgenic Bt corn producing the Cry1Fa toxin is the principal strat- egy for the control of The fall armyworm Spodoptera frugiperda, that is the most important lepidopteran pest of corn in South American countries and has evolved resistance to this toxin. It has been shown that insects resistant to Bt toxins can have costs of reproduction resulting in a reduction of off- spring production. One way of assessing the possible effects of resistance on the reproduction of S. frugiperda is by evaluating the fecundity and fertility of females. So, we mated susceptible and resistant virgin and mated males of different ages with virgin females and measured the fecundity and fertil- ity. The fecundity and fertility were lower for resistant females mated with resistant mated males than for susceptible females mated with susceptible ex- perienced males. To figure out if the spermatophore transferred by males has some effect on the results above, we mated virgin and mated males of differ- ent ages with virgin females and measured the weight of the spermatophores. The spermatophore weight was lighter for resistant females mated with resis- tant mated males than for susceptible females mated with susceptible mated males. Since the spermatophore also contains nutrients that are used by the females to fecundate their eggs, it can explain the fecundity results. Our data provided clear evidence that the development of Bt resistance affected the reproductive capacity of resistant mated males of S. frugiperda and that this effected the reprodutive output of females mated with this males.